High-throughput flowing upstream sperm sorting in a retarding flow field for human semen analysis. Issue 6 (21st February 2017) - Wu, Jen-Kuei; Chen, Peng-Chun; Lin, Yu-Nan; Wang, Chia-Woei; Pan, Li-Chern; Tseng, Fan-Gang
Abstract : In this paper, we propose a microfluidic device capable of generating a retarding flow field for the sorting and separation of human motile sperm in a high-throughput manner. Abstract : In this paper, we propose a microfluidic device capable of generating a retarding flow field for the sorting and separation of human motile sperm in a high-throughput manner. The proposed sorting/separation process begins with a rapid flow field in a straight-flow zone to carry sperm into a sorting zone to maintain the sperm's mobility. The sorting zone consists of a diffuser-type sperm sorter to differentiate sperm with different motilities based on the flowing upstream nature of human sperm in a retarding flow field. The dead sperm will then be separated from the live ones by passing through a dumbbell flow field to the outlet for disposal. The proposed flowing upstream sperm sorter (FUSS) is designed to imitate the selection mechanism found in the female body when sperm swim into the uterus. The experimental results demonstrate the utility of this device with regard to throughput (approximately 200 000 sperm per minute and a maximum of 200 million cells per mL), efficiency (90% of selected sperm are mobile), and the ability to select sperm with high motility (∼20% of sperm with a velocity exceeding 120 μm s −1 ). The proposed device is suitable for intrauterine insemination as well as in vitro fertilization thanks to the highly efficient sorting process not interfering with the natural function and energy resource of human sperm.